Analisis Program Lampung Begawi dalam Memperkenalkan Budaya dan Produk Unggulan UMKM Provinsi Lampung - Laura Gayatri; Desika Fitriana; Martines Sabiliun Muttaqina; Elza Zeriana; Berchah Pitoewas; Abdul Halim (GLOBAL SCIENTS PUBLISHER, 2025)
This research aims to describe the implementation of the Lampung Begawi Program as a strategy for promoting local culture while simultaneously empowering MSMEs (Micro, Small, and Medium Enterprises) in Lampung Province, and to formulate strategic recommendations for its sustainable development. Lampung Begawi is an annual program that integrates cultural festivals, MSME product exhibitions, training workshops, and multi-stakeholder collaboration in one platform. This study adopts a mixed-methods approach by combining qualitative and quantitative data through document analysis, in-depth interviews, and surveys targeting participants and MSME actors. The findings indicate that the program has successfully increased cultural exposure and generated tangible economic benefits for MSMEs, including revenue growth, digital market access, and expanded business networks. However, several challenges remain, such as limited funding, insufficient professional digital branding, and low participation from rural-based MSMEs. The study recommends strategies such as branding enhancement, establishment of an endowment fund, digital partnership with online marketplaces, and strengthening local government’s role in mentoring and capacity building. Conceptually, this research contributes to the development of an integrated evaluation model that links cultural preservation with community-based creative economy. With a collaborative approach, Lampung Begawi holds potential as a national model for synergy between cultural revitalization and local economic empowerment.